Zasady i reguły. Pewność prawa podatkowego a ślepa ulica konkretu - Filipczyk, Hanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The purpose of the article is to discuss and critically evaluate the legislative model adopted in lawmaking of the tax law. The model is premised upon the strategy of striving towards the maximal available precision determinacy of legal norms through constructing the multitude of detailed prescriptive legal rules. In practice this legislative style is combined with, and goes hand in hand with textualism: aposition advocating adherence to the linguistic directives arguments of legal interpretation. As aresult, the communicativeness and clarity of tax law are impaired.In the article an alternative model is postulated, entailing that tax law is based not only on legal rules but also, if not primarily, on legal principles in case of conflicts prevailing over rules, and that in drafting legal provisions open-ended and general formulas expressions are used. Contrary to what is commonly believed, this legislative model and the corresponding drafting technique are not detrimental to legal certainty. It is argued that the opposite is true: they can serve the purpose of legal certainty better that the current model does, while at the same time improving the effectiveness of efforts to combat tax avoidance.
Keywords: prawo podatkowe; model legislacyjny; krytyczna ocena